2020
DOI: 10.1111/issr.12243
|View full text |Cite
|
Sign up to set email alerts
|

Social protection and revenue collection: How they can jointly contribute to strengthening social cohesion

Abstract: Social protection and revenue collection are often regarded as potential drivers of social cohesion. The article joins this debate, providing three main contributions. First, we carefully discuss the concept of social cohesion and endorse one specific definition. Second, we propose using the concept of the "fiscal contract" as the key theoretical lens to understand the often neglected potential joint effects of social protection and revenue collection policies on social cohesion. Third, we illustrate three mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In addition, we assume social protection schemes strengthen vertical trust —at least if they are implemented or financed by the state (Burchi et al 2020 ; Haider and Mcloughlin 2016 ; Loewe and Zintl 2021 ). Their beneficiaries are likely to be grateful to the actors that support them financially or by providing efficient instruments to deal with risk and poverty.…”
Section: Conceptual Framework: Relationship Between Social Protection...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we assume social protection schemes strengthen vertical trust —at least if they are implemented or financed by the state (Burchi et al 2020 ; Haider and Mcloughlin 2016 ; Loewe and Zintl 2021 ). Their beneficiaries are likely to be grateful to the actors that support them financially or by providing efficient instruments to deal with risk and poverty.…”
Section: Conceptual Framework: Relationship Between Social Protection...mentioning
confidence: 99%
“…Social protection thereby establishes a stronger relation between citizens and the government (Babajanian 2012 ). As a result, citizens tend to be more willing to accept their current government and the given political order, and to invest in public goods such as public order, the tidiness of streets or communal action (Burchi et al 2020 ; Loewe et al 2020 ). This effect on vertical trust is found to be especially relevant in climate change mitigation policies, where both cash transfers and trust in government play a key role (Klenert et al 2018 ).…”
Section: Conceptual Framework: Relationship Between Social Protection...mentioning
confidence: 99%
“…The definition includes three attributes, each of them examined in both dimensions, horizontal and vertical. Following Leininger et al ( 2021a ) and Burchi et al ( 2020 ), the attributes are as follows. Trust Trust is an important component of social cohesion (Chan et al 2006 ; Dragolov et al 2013 ; Langer et al 2017 ; Schiefer and van der Noll 2017 .…”
Section: Concept Of Social Cohesion and Theoretical Considerationsmentioning
confidence: 99%
“…A further important factor is that governments must highlight that the state plays a key role in the financing and/or management of social protection programmes in times of shocks. Beneficiaries can take that as a signal that the state cares about their interests, which in turn can increase trust in public institutions (Burchi et al 2020 ). When social protection measures are communicated as a response of national unity to deal with the shock, it may also improve the beneficiaries feeling of belonging ( inclusive identity ).…”
Section: Concept Of Social Cohesion and Theoretical Considerationsmentioning
confidence: 99%
“…Conditional cash transfer schemes can even contribute significantly to the trust of households in political leaders, as Evans et al (2019) showed for Tanzania. This can be due to three effects: first, citizens' appreciation of government commitment to social welfare; and second, a reduction in poverty and inequality; and third, social protection spending that can foster growth and thereby reduce the opportunity costs of being part of an armed group (Babajanian 2012;Burchi et al 2020;Koehler 2021;Mallet and Slater 2013;Reeg 2017;van Ginneken 2005).…”
Section: States Failing On the Delivery Of Provisionmentioning
confidence: 99%